Engendering cities: international dimensions from Aotearoa, New Zealand - Reeves, Dory; Zombori, Eva (Town planning review)
This paper contributes a New Zealand perspective to this special issue on engendering cities by considering what a gender approach to planning involves. It examines the New Zealand approach and why it has not embraced a gender sensitive approach to planning and the role played by Maori. It discusses how the EU-New Zealand Agreements, linked to the European Growth Strategy 2020 (European Commission, 2010) and the associated research strategy Horizon 2020 (European Commission, 2011a), could deliver gender sensitive responses to planning in New Zealand. It asks what role the pilot international genderSTE network could play and what challenges need to be overcome. The investigation found that: (1) New Zealand's approach to gender has been, and continues to be, gender neutral. A specific issue-based approach has been a feature of New Zealand, resulting in a lack of gender visibility in planning; (2) the subordination of the feminist discourse to Maori issues is a feature of New Zealand; and (3) the NZ-EU Science Agreements, linked to Horizon 2020, could potentially help to deliver gender sensitive responses to planning in New Zealand and fledging international networks, such as genderSTE, could also potentially play an important role in providing mutual support to groups in New Zealand, advocating for progress.